2009
DOI: 10.1590/s0102-86502009000500008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an extract of Aloe vera on the biodistribution of sodium pertechnetate (Na99mTcO4) in rats

Abstract: PURPOSE: Aloe vera is a tropical plant popularly known in Brazil as babosa. We have investigated the effect of aqueous extract of Aloe vera on the biodistribution of Na99mTcO4 and laboratorial parameters in Wistar rats. METHODS: Twelve animals were divided into treated and control groups. In the treated group, Aloe vera was given by gavage (5mg/mL/day) during 10 days. The control group received sorbitol by the same way and period. One hour after the last dose, we injected 0.1mL of Na99mTcO4 by orbital plexus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
(35 reference statements)
1
9
0
Order By: Relevance
“…However, liver toxicity is a potential complication of these herbal compounds that may lead to liver failure, as demonstrated in studies described by Holanda et al 7 Adeyemi et al 12 showed in their study that there was a significant reduction in the concentration of blood glucose in diabetic rats treated with Anonna muricata (soursop), a result not found in our study, possibly due to the low extract concentration used. High levels of unsaturated fatty acids seem to play important role in improving the lipid profile, both in humans and in animals, being appointed more substantial effect on reducing low density lipoprotein (LDL), considered a cardiovascular risk factor 13 .…”
Section: Organssupporting
confidence: 41%
See 4 more Smart Citations
“…However, liver toxicity is a potential complication of these herbal compounds that may lead to liver failure, as demonstrated in studies described by Holanda et al 7 Adeyemi et al 12 showed in their study that there was a significant reduction in the concentration of blood glucose in diabetic rats treated with Anonna muricata (soursop), a result not found in our study, possibly due to the low extract concentration used. High levels of unsaturated fatty acids seem to play important role in improving the lipid profile, both in humans and in animals, being appointed more substantial effect on reducing low density lipoprotein (LDL), considered a cardiovascular risk factor 13 .…”
Section: Organssupporting
confidence: 41%
“…Several experimental models have been used to evaluate the properties of synthetic and natural drugs [6][7][8] . The biodistribution of radiopharmaceuticals in the animal organism can be changed with concomitant use of drugs natural and/or synthetic, certain diets, parasitic infections, the use of cigarettes and surgery, as demonstrated in studies described by Araújo-Filho et al 15 and Rêgo et al 16 .…”
Section: Organsmentioning
confidence: 99%
See 3 more Smart Citations